The Effect of Resilience and Self-Concept on the Work Ethic of Elementary School Teachers in Kuantan Hilir District - Maryunis , Maryunis; Putra, Jaya Adi; Kurnia, Rita (Journal Corner of Education, Linguistics, and Literature, 2025)
The work ethic of teachers is an essential factor in improving the quality of education in elementary schools within Kuantan Hilir Seberang District. Teachers with a strong work ethic demonstrate discipline, responsibility, professionalism, innovation, and dedication, thereby creating a conducive and positive learning environment. Internal factors such as resilience and self-concept play a significant role in shaping this work ethic. Teachers with high resilience are better able to cope with job-related pressures and administrative challenges, remain productive, and sustain both self-motivation and student motivation. A positive self-concept enhances teachers’ confidence, commitment, and professionalism. Observations indicate that several teachers still require improvement in discipline, innovation, and competency development. Strengthening these internal aspects can enhance overall work ethic and directly contribute to improving educational quality. This study addresses the following research questions: (1) Is there an influence of resilience on the work ethic of elementary school teachers in Kuantan Hilir Seberang District? (2) Is there an influence of self-concept on the work ethic of these teachers? (3) Is there a combined influence of resilience and self-concept on their work ethic? This research employs a quantitative approach using an ex post facto research design. The study examines three variables to determine the extent of influence between the independent and dependent variables. The independent variables are resilience (X1) and self-concept (X2), while the dependent variable is work ethic (Y). The population of this study consists of all elementary school teachers in Kuantan Hilir Seberang District, totaling 125 teachers across 10 schools. The sample comprises 96 teachers from the same 10 schools, selected using a cluster random sampling technique. Data processing and analysis were conducted using descriptive profile analysis, descriptive statistics, and inferential statistics. The data were analyzed using SPSS version 25. The findings of this research indicate: (1) a significant and positive influence of resilience on the work ethic of elementary school teachers, with an effect size of 45.9%; (2) a significant and positive influence of self-concept on work ethic, with an effect size of 42.6%; and (3) a significant and positive combined influence of resilience and self-concept on work ethic, with an overall effect size of 47.3%. This indicates a moderate level of influence, as the remaining 52.7% is attributed to other factors not examined in this study.